2016
DOI: 10.5511/plantbiotechnology.16.0215b
|View full text |Cite
|
Sign up to set email alerts
|

ANAC075, a putative regulator of VASCULAR-RELATED NAC-DOMAIN7, is a repressor of flowering

Abstract: Fine-tuning of flowering timing is crucial for plants to survive and leave offspring and depends on various endogenous and environmental factors. Here we report the identification of a vascular transcription factor, ANAC075, a putative regulator of VASCULAR-RELATED NAC-DOMAIN7 (VND7), as a negative regulator of flowering in Arabidopsis. Loss of function of ANAC075 causes the upregulation of floral integrator genes and early flowering under both long-and short-day conditions. ANAC075 promoter activity was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
0
11
1
Order By: Relevance
“…These regions contained 1220 genes (Additional file 2 : Table S13) with functions relating to binding, metabolic process, cellular process, biological regulation, localization, and response to stimulus (Additional file 2 : Table S14). Many well-studied genes involved in the regulation of flowering, cell wall synthesis, and adaptation were identified, such as Rc10G022330 encoding a putative orthologue of TERMINAL FLOWER 1 (TFL1) that plays a critical role in the regulation of inflorescence meristem identity, flowering time, and plant height in Arabidopsis [ 32 , 33 ]; Rc03G005883 encoding a putative SNW/SKI-interacting protein (SKIP) that involved into the regulation of environmental fitness and floral transition in Arabidopsis [ 34 ]; Rc03G005826 encoding a NAC transcription factor, homologous to Arabidopsis ANAC075 that functions as a repressor of flowering and involved in secondary cell wall formation [ 35 , 36 ]; Rc04G007260 encoding a member of the R2R3 gene family (MYB46), which involved in the control of secondary cell wall thickening [ 37 ]; Rc05G010832 encoding a gibberellin 2-oxidase (GA2OX2) which had a functional role in the control of plant growth and height by regulating GA concentrations in aspen trees [ 38 ]; and two genes, Rc02G003752 and Rc02G003753, putatively encoding gibberellin-regulated proteins (Additional file 2 : Table S13).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These regions contained 1220 genes (Additional file 2 : Table S13) with functions relating to binding, metabolic process, cellular process, biological regulation, localization, and response to stimulus (Additional file 2 : Table S14). Many well-studied genes involved in the regulation of flowering, cell wall synthesis, and adaptation were identified, such as Rc10G022330 encoding a putative orthologue of TERMINAL FLOWER 1 (TFL1) that plays a critical role in the regulation of inflorescence meristem identity, flowering time, and plant height in Arabidopsis [ 32 , 33 ]; Rc03G005883 encoding a putative SNW/SKI-interacting protein (SKIP) that involved into the regulation of environmental fitness and floral transition in Arabidopsis [ 34 ]; Rc03G005826 encoding a NAC transcription factor, homologous to Arabidopsis ANAC075 that functions as a repressor of flowering and involved in secondary cell wall formation [ 35 , 36 ]; Rc04G007260 encoding a member of the R2R3 gene family (MYB46), which involved in the control of secondary cell wall thickening [ 37 ]; Rc05G010832 encoding a gibberellin 2-oxidase (GA2OX2) which had a functional role in the control of plant growth and height by regulating GA concentrations in aspen trees [ 38 ]; and two genes, Rc02G003752 and Rc02G003753, putatively encoding gibberellin-regulated proteins (Additional file 2 : Table S13).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…1a; Zhong et al ., 2011b). Although expression of SND4/ANAC075 fused with the VP16 activation domain in nst1/3 fiber cells was able to reinstate their secondary wall thickening (Sakamoto & Mitsuda, 2015), a recent study concluded that SND4/ANAC075 was not involved in secondary wall formation and instead, it was a negative regulator of flowering based on the findings that the GUS reporter gene driven by its promoter was mainly expressed in the phloem and its mutation resulted in early flowering but no phenotypes associated with secondary walls (Fujiwara & Mitsuda, 2016). Since the promoter of SND4/ANAC075 used in that study may not encompass all the cis‐elements dictating its bona fide expression, we set out to re‐examine its expression pattern.…”
Section: Resultsmentioning
confidence: 99%
“…While the function of ANAC099 has not yet been studied, ANAC075 was shown to activate the VND7 promoter (Endo et al ., 2015) and expression of VP16‐fused ANAC075 in nst1/3 fiber cells was able to reinstate their secondary wall thickening (Sakamoto & Mitsuda, 2015). However, one study reported that the ANAC075 gene was mainly expressed in the phloem and suggested that it was not involved in secondary wall formation (Fujiwara & Mitsuda, 2016). Although it is uncertain whether ANAC075 plays a role in regulating secondary wall biosynthesis, it has been shown that its poplar orthologs, PtrNAC150 and PtrNAC151, are wood‐associated, PtrWND2B‐regulated transcription factors that can activate the promoters of several biosynthesis genes for secondary wall cellulose, xylan and lignin (Zhong et al ., 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…There are one additional NAC gene and one additional MYB gene in the top 10 genes of the pink module but they are not annotated with the TF GO term. Sobic.003G035100 (SbNAC75a) is a close homolog of NAC075, a putative regulator of VASCULAR RELATED NAC-DOMAIN PROTEIN 7 (VND7, Supplementary Figure S4B) which is a master regulator of vessel SCW deposition in Arabidopsis (Endo et al, 2015;Fujiwara and Mitsuda, 2016). Sobic.001G110900 is a homolog of AtMYB52/54, another regulator of SCW (Zhong et al, 2008).…”
Section: Identification Of Hub Genes In the Cell Wall Enriched Modulesmentioning
confidence: 99%